2013
DOI: 10.1007/s00264-013-2211-z
|View full text |Cite
|
Sign up to set email alerts
|

Multi-plate reconstruction for severe bicondylar tibial plateau fractures of young adults

Abstract: Purpose This study was to evaluate clinical outcomes and complications following multi-plate reconstruction for treating severe bicondylar tibial plateau fractures of young adults. Methods Between September 2007 and February 2012, 26 patients with severe bicondylar tibial plateau fractures met inclusion criteria; they were treated using multi-plate technique through combined approaches. Patients received an average follow-up of 40.8 (range, 18-64) months, which included anteroposterior and lateral imaging, pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 20 publications
0
23
1
Order By: Relevance
“…With the combination of a heavy lateral locking plate and multi medial-posterior small antiglide plates, good results were achieved in 12 patients in the preliminary report [7]. Zhai et al [26] reported their experience with applying multi-plates (3-, 4-, and 5-plates) for severe and complicated bicondylar tibial plateau fractures in 26 young patients. They used 3.5-mm T-plates for the medial and posterolateral fragments, and a heavy locking plate for the splitdepressed anterolateral fragment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the combination of a heavy lateral locking plate and multi medial-posterior small antiglide plates, good results were achieved in 12 patients in the preliminary report [7]. Zhai et al [26] reported their experience with applying multi-plates (3-, 4-, and 5-plates) for severe and complicated bicondylar tibial plateau fractures in 26 young patients. They used 3.5-mm T-plates for the medial and posterolateral fragments, and a heavy locking plate for the splitdepressed anterolateral fragment.…”
Section: Discussionmentioning
confidence: 99%
“…For those complex bicondylar fractures, anatomic reduction of the PM fragment is of paramount importance [4,7,26,27]. By exact reposition of the distal V-shaped fracture spike, the fragment height and tilt angle can be anatomically restored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the use of two plates can expose difficulties when implanting a total knee arthroplasty, with the obligation to remove the plates through two incisions and a longer surgery time. Some authors proposed a multiplate reconstruction for severe bicondylar tibial plateau fracture, especially for young adults, with three to five plates [23]. In order to reduce cutaneous and septic complications a double mini-invasive surgical access was proposed.…”
Section: Discussionmentioning
confidence: 99%
“…The operations were all performed by the same chief surgeon (ChenShou Lin). All cases were treated with reduction and internal fixation through combined approaches [4] (Fig. 2a), i.e.…”
Section: Methodsmentioning
confidence: 99%